Industrialization and environmental health in Poland - Indulski, J A; Rolecki, R (Central European journal of public health, 1995)
There has been enormous pollution and biodegradation of environment in Poland as the consequence of industrialization developed regardless the principles of sustainable development. In the recent years, the decrease of total emission of air pollution caused by gases and dust, the decrease of emission of unprocessed sewage and industrial waste can be seen. These facts are the consequences of economic recession which have appeared in Poland along with economic transformation. However, there is still significant escalation of environmental pollution, in so-called areas of ecological hazards. There are heavily industrialized and urbanized areas covering about 10% of the total country area but inhabited by over 30% of the total country population. The significant environmental pollution goes together with deterioration of the country's health situation what can be seen in shortening the average lifetime expectancy, increased frequency of cardiovascular diseases and cancers and higher infants death rate in comparison to other European countries. Considering the complexity of the factors affecting the population's health status, the basis of the health and environmental policy conceived in order to stop and alter the unwanted health condition tendencies and the environmental quality have been shown here.
Keywords: zdravotní politika; Female; Polsko; ženské pohlaví; lidé; znečištění životního prostředí; politika; Environmental Health; Industry; Environmental Pollution; Health Policy; Male; průmysl; Socioeconomic Factors; environmentální zdraví; Politics; socioekonomické faktory; mužské pohlaví; Poland; Humans